Administering Fiscal Regimes for Extractive Industries. - Calder, Jack (International Monetary Fund, 2014)
Revenues from natural resources often pose unique challenges for tax administration. This Handbook is one of the first of its kind to focus attention on effectively administering revenues from extractive industries. It provides policymakers and officials in developing and emerging market economies with practical guidelines to establish a robust legal framework, organization, and procedures for administering revenue from these industries. It discusses transparency and how to promote it in the face of increasing demands for clarity and accountability in the administration of public revenues from.